Determinan yang Mempengaruhi Kejadian ISPA pada Masyarakat di Wilayah Kerja Puskesmas Sunggal Kota Medan - Nisa, Widiya; Nasution, Febri Aini; Syafei, Atikah Nadiah; Apriliani, Apriliani; Lauta, Aurora Putri; Salsabila, Zahra (Persatuan Dosen Kesehatan Masyarakat, 2026)
ISPA is a disease that can attack the upper and lower respiratory tract that can be caused by several infectious agents that not only involve individual morbidity but also burden health services, and a person's productivity. This study aims to understand the prevalence of ISPA and risk factors that affect the community in the work area of the Sunggal Community Health Center, Medan City in 2025. The study used a descriptive analytical method with a cross-sectional design involving 314 respondents. Data were collected through questionnaires and analyzed using the chi-square test. The results of the bivariate analysis showed that age, smoking habits and preventive measures had a significant relationship with the incidence of ISPA. Age correlates with the incidence of ARI (p=0.034), where young adults have a higher proportion of ARI (59.6%) than older adults (47.7%). Smoking habits are significantly associated with the incidence of ARI (p=0.001), respondents who smoke are more likely to experience ARI (66.4%) than non-smokers (47.1%). Preventive action variables are also significantly associated with the incidence of ARI (p=0.002), with a tendency that the worse the action, the higher the incidence of ARI (inadequate action 75.6%, sufficient 54.5%, good 44.2%). Meanwhile, the variables of gender (p=0.215), last education (p=0.066), occupation (p=0.115), knowledge (p=0.313), and attitude (p=0.982) do not show a significant relationship with the incidence of ARI. ARI control efforts should not only focus on case therapy but must strengthen promotive and preventive efforts as well as risk management at the family and community levels. Keywords: ISPA, Determinants, Health Behavior